دور التنمية السياسية في استقرار النظام السياسي في البلدان العربية - حبيب, زينة (Latakia University Journal - Economic and Legal Sciences Series, 2018)
استهدفت الدراسة الوقوف على دور التنمية السياسية في استقرار الأنظمة السياسية في الدول العربية وانعكاسات ذلك على المشاركة السياسية، حيث كانت مشكلة الدراسة تدور حول سؤال محوري مفاده : ما دور التنمية السياسية في الدول العربية وأثرها على الاستقرار السياسي ؟ وكيف تؤثر تلك العمليات على المشاركة السياسية ؟ وما المتغيرات المتعلقة بالمفاهيم التالية : الديمقراطية ، المشاركة السياسية، بناء منظمات المجتمع المدني ضمن سياق مصطلح التنمية السياسية ؟.. أما فرضية الدراسة فتتمحور حول فكرة أساسية مفادها : أن لعمليات التنمية السياسية دوراً في تحقيق الاستقرار السياسي في الدول العربية، وذلك نتيجة الاستجابة لمتطلباتها المتعلقة بالديمقراطية، والمشاركة السياسية، والحرية ، والعدالة وبناء منظمات المجتمع المدني، وبمساعدة الأحداث المتسارعة والتغييرات التي أصابت المجتمعات البشرية في مجال التنمية السياسية، وللتحقق من صحة الفرضية والإجابة عن أسئلة الدراسة فقد تم استخدام المنهج التاريخي والمنهج التحليلي الوصفي إلى جانب الأخذ بمنهج النظم في العلاقات الدولية لكونها المناهج الأنسب في تناول مثل هذه الدراسات . لقد أوصلتنا الدراسة إلى صحة فرضية الدراسة وتم استخلاص عدة نتائج أهمها : أنّ عمليات التحول الديمقراطي التي تقع ضمن جهود التنمية السياسية مرت بالعديد من التحولات والمراحل إلاّ أنّ معظم النظم السياسية العربية قد شهدت انقطاعاً حاداً في مسيرة تطورها التاريخي، وذلك بعد ما يسمى " الربيع العربي " وقد استوجبت الدراسة عدة توصيات أهمها : 1- الحفاظ على مبدأ الشفافية عند المباشرة بالفعاليات الحكومية والقطاعات الأخرى المهمة في المجتمع . 2- الاهتمام بقنوات الاتصال بين الأفراد العاديين وأجهزة السلطة . 3- نشر الوعي بالحقوق المدنية والسياسية وصيانتها . This study aimed identify the role of political development in the stability of the Arab countries and the implications for political participation, where the problem of the study revolves around a central question that views: what the role of political development in the Arab countries and its impact on political stability?And how these processes affect political participation? What are the variables related to the following concept?Democracy, political participation, build civil society organizations within the context of the term political development? .. the study hypothesis is centered on the fundamental premise that: the development processes political role in achieving political stability in the Arab countries .. as a result of responding to the requirements of democracy, political participation, freedom, justice, and building civil society organizations, with the help of fast-moving events and changes that have affected human societies in the area of political development., And to verify the validity of the hypothesis and to answer the questions of the study has been using the historical method and descriptive approach, along with the introduction of systems approach in international relations, being a curriculum best suited to address such studies.Findings of this study showed that the hypothesis is true, and we concluded to the following results. The processes of democratic change which fell under the political development under went many changes and faces: Most of the political Arabic regemes faced difficulties in their historical development progress after the so called “ Arabic Spring ”.This study has necessitated several recommendations including:1. Maintaining the principle of transparency when direct government events and other impotant sectors of society.2. Interest in the channel of communication between ordinary people and power devices.3. A wareness on Civil and Political Rights and maintenance.